The State as an Engine of Inclusive Sustainable Economic Growth and Development - Acquah-Sam, Emmanuel (European Scientific Journal, ESJ, 2020)
This paper is a qualitative analysis of the critical role of government in promoting inclusive sustainable economic growth and development. This critical role of government transcends beyond an economy’s experience of normal economic life or economic crisis, the type of economic system that is being practiced by a nation, and the level of development of a nation. The reason is that government serves as a stimulator, driver, sparker, lubricator, and the co-ordinator of the other economic units to create a conducive environment needed for private sector growth and the overall development of an economy. Though, the state also has its deficiencies in resource allocation and the management of the economy, a poorly functioning government portends economic doom. The exclusive roles of governments in promoting inclusive sustainable economic growth and development are: smoothening markets activities, promoting better macroeconomic performances, driving, sparking, stimulating, and lubricating the private sector for growth, mitigating social vices, undertaking financial sector cleanup, stabilisation, restructuring, providing stimulus packages to address economic meltdowns or recessions, and combating pandemics. This study concludes that the state serves as an engine of inclusive sustainable economic growth and development. This study recommends that governments must be held accountable by their citizenry and the international community for their actions and inactions and should be prevented from shirking their responsibilities to their societies. They need to be more efficient and proactive in ensuring public sector efficiency so as to spearhead economic growth and development. Again, the roles of the state and the private sector in promoting inclusive sustainable economic growth and development must not be mutually exclusive. Every economy must strive for a healthy balance between private sector and state planning that will lead to inclusive sustainable economic growth and development. Governments must promote effective governance and combat corruption both in the private and public sectors of every economy.